Analysis of inter-examination differences in sperm nuclear vacuoles among male patients with infertility. (February 2014) - Komiya, Akira; Watanabe, Akihiko; Kawauchi, Yoko; Fuse, Hideki
Abstract We analyzed the inter-examination differences in sperm nuclear vacuoles among male patients with infertility. We enrolled 56 male patients with infertility who underwent multiple semen analyses and high-magnification observation of the sperm head. A total of 162 ejaculates were evaluated. The average patient age was 34.5 years. Following the conventional semen analysis, the nuclear vacuoles in motile spermatozoa were evaluated at 3700–6150 × magnification on an inverted microscope equipped with differential interference contrast optics. A large sperm nuclear vacuole (LNV) was defined as one or more vacuoles with a maximum diameter exhibiting >50% width of the sperm head. We compared the differences in the proportion of spermatozoa with LNVs between two consecutive semen samples before treatment. Treatment-related differences in the number of LNVs were also analyzed. Student's t-test was used to perform the statistical analyses. No differences were observed in any semen parameters between the first and second ejaculates. On high-magnification microscopy, the proportion of spermatozoa with LNVs was 23.5% and 29.4% (p = 0.0220) in the first and second ejaculates, respectively in 33 patients. Among the 18 patients who underwent varicocele repair using a microsurgical subinguinal approach, the proportion of spermatozoa with LNVs at baseline, three, and six months after surgery was 27.7%, 12.0% (p = 0.0132 versus baseline), and 10.3% (p = 0.0226 versus baseline), respectively. After three months of medical treatment for male infertility in 28 patients, the proportion of spermatozoa with LNVs slightly decreased from 33.3% to 28.6% (p = 0.1276); however, it was not statistically significant. In conclusion, when multiple ejaculates were obtained, in the subset of male patients with infertility, the proportion of spermatozoa with LNVs could be different. The number of LNVs decreased following varicocele repair.